MODEL KONSELING KELUARGA UNTUK MENGEMBANGKAN KESIAPAN MENTAL CALON TENAGA KERJA WANITA (TKW) DAN KELUARGANYA - Santoso, - (2010)
Santoso, 2010. A Model of Family Counseling to Enhance Mental Readiness of Prospective Women Migrant Workers and Their Families. A Dissertation guided by Prof. Dr. Rochman Natawidjaja (Promoter), Prof. Dr. S.P. Sukartini, M.Pd. (Co-Promoter) and Prof. Dr. Syamsu Yusuf L.N., M.Pd. (Member). The background of this research was the empirical fact on the increase of mental unreadiness symptoms among prospective women migrant workers and their families along with all of the psychological implications that signaled the need for family counseling. Family counseling is an interactive process to assist family members in reaching harmonious or balanced psychological conditions to gain happiness. This research is aimed to producing a effective model of family counseling to enhance mental readiness of prospective women migrant workers and their families. The study applies R & D approach, using mixed methods design. With the exploratory type. The model effectiveness is tested applying pre-posttest experimental design. The subjects of this research are nuclear families consisting of husbands, wives, and children. The selection of subjects in this research were determined to be prospective women migrant workers who were married either with or without children recruited by PPTKIS (Private Indonesian Migrant Worker Employment Agency) in Kendal Regency. The results of this research are first, family counseling model is effective in enhancing mental readiness of the prospective women migrant workers and their families. Second, mental readiness of prospective women migrant workers and their families before treated with family counseling was low. Third, mental readiness of prospective women migrant workers and their families after family counseling are high. Fourth, there is a significant difference in terms of mental readiness of prospective women migrant workers and their families before and after the treatment of family counseling, either as a whole or each of its aspects or its indicators. Fifth, the expert rational validation, proves that asked the family counseling model is appropriate to be used as counseling intervention. The asked is recommended to applied by PPTKIS, Guidance and Counseling Programs, prospective women migrant workers and their families, and further researchers. Key word: Model of Family Counseling, Mental Readiness, Women Migrant Workers.